Rethinking Comprehensive HIV/AIDS Intervention Strategy - Zhipeng SUN; Meixia YANG (Yixue yu zhexue)
This paper begins with the long-standing separation between "individual agency" and "social structure" in HIV/AIDS intervention strategies, and reviews the evolution of various intervention approaches. It focuses on the theoretical foundations, values, and challenges associated with different intervention strategies. Comprehensive HIV/AIDS intervention is not merely a simple combination of behavioral, biomedical, and structural methods, nor can it automatically bridge the gap between agency and structure inherent in intervention practices. From the theoretical perspective of social public health, by addressing inequalities and other structural barriers impeding effective HIV/AIDS interventions, mobilizing and empowering community-based organizations, respecting individual rights, and attending to their practices and lifeworld, it becomes feasible to bridge individual agency and social structure, thereby offering a pragmatic pathway for integrated, comprehensive HIV/AIDS interventions.